Abandono familiar y su repercusión en la salud mental de un adulto mayor de 78 años de la ciudad de Babahoyo - Carrasco Mancheno, Vivian Simone (2022)
The present case study was developed with the purpose of describing the repercussion caused by family abandonment in the mental health of an adult over 78 years of age in the city of Babahoyo, as is currently known, this problem has a direct affectation to older adults because they are going through a stage of fragility, in which they require more attention and care from their relatives and when this breaks down or disappears, this vulnerable population can experience both physical and psychological problems, which immediately affect mental health of older adults. For the investigation and data collection, the qualitative and quantitative method was used, and the use of different tools such as clinical history, clinical observation and the different tests that help establish a presumptive diagnosis for the patient, finally the findings that were found in the different areas and we proceed with the elaboration of a proposal or psychotherapeutic plan with the use of different techniques under the approach of Cognitive Behavioral Therapy (CBT) with the sole purpose of providing the patient with possible solutions to the patient's problem.